An analytical film drainage model and breakup criterion for Taylor bubbles in slug flow in inclined round pipes. (September 2016) - Lizarraga-Garcia, E.; Buongiorno, J.; Bucci, M.
Highlights: Study of the drainage of the thin film above Taylor bubbles in inclined pipes that includes gravity, surface tension and intermolecular forces. Analytical model predicting the gravity-driven drainage of the lubricating film above Taylor bubbles in inclined pipes. Criterion to avoid film breakup in Taylor bubble flow derived from the drainage model. Criterion applicable to determine the film existence for numerical simulations and mechanistic modeling of slug flow, as well as flow assurance studies. Experimental model validation. Abstract: The velocity of Taylor bubbles in inclined pipes is reduced if a lubricating liquid film between the bubble and the pipe wall is not present. An analytical model predicting the gravity-driven drainage of the lubricating film is presented in this article. The model is then used to establish a criterion for film breakup: if t ¯ b u b b l e = t b u b b l e / τ < 0.01 the thin film would not break up, where tbubble is the bubble's passage time, and τ is the characteristic film drainage time based on the fluid properties, pipe geometry, and critical film thickness. The model is validated experimentally with Taylor bubbles in inclined pipes (5° to 90°, the latter being vertical) with stagnant liquids (ethanol, methanol, and mixtures of deionized water and methanol).